Effect of Using Wii Balance Board on Functional Balance of Children With Ataxic Cerebral Palsy - Seyed Mehdi Hosseini; Mohsen Vahedi; Ebrahim Pishyareh; Saeid Fatorehchy; Elham Shakiba (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: Ataxic cerebral palsy accounts for 5%-10% of the population with cerebral palsy. This palsy is characterized by poor balance and coordination, clumsiness, and involuntary tremor. As a result, balance training is one of the essential parts of the rehabilitation programs for children with ataxic cerebral palsy. Wii Balance Board (WBB) is an efficient tool for balance training in children with different physical problems, including cerebral palsy. This study aims to assess the effect of WBB-based balance training on functional balance and the persistence of its effect two months after the intervention in children with ataxic cerebral palsy. Materials & Methods: This is a single-case study with a pre-test, post-test and follow-up design conducted on 3 children (2 girls and 1 boy) with ataxic cerebral palsy (Mean±SD age=10.56±1.09 years). They were classified at levels I and II of the gross motor function classification system. They received conventional occupational therapy three sessions per week, each for 45 minutes in the baseline and follow-up phases. In the intervention phase, each session consisted of 25 minutes of routine rehabilitation followed by 20 minutes of WBB-based balance training for 3 months (12 hours). The changes were evaluated by the Pediatric Balance Scale (PBS) and Timed Up And Go (TUG) test, three times in the baseline phase, three times in the intervention phase (at the end of 12th, 24th, and 36th sessions), and two times in the follow-up phase (one and two months after the intervention). Assessments were done by a pediatric occupational therapist who was unaware of the study process. Finally, the results were analyzed using the Percentage of Nonoverlapping Data (PND), 2 Standard Deviations (2SD), Hedges's g, and the visual analysis method. Results: The results of the PBS and TUG test showed the improvement of functional balance in all children in the intervention phase and maintained in the follow-up phase. The PND of PBS and TUG test results was 100% for all children, indicating that balance training by the WBB improved functional balance in the intervention and follow-up phases compared to the baseline. Hedeges' g value for all participants was more than 0.8, indicating a significant difference between the baseline and follow-up phases. The 2SD results showed a significant increase in the PBS score and a significant reduction in the TUG test duration in all children. Furthermore, the visual analysis revealed a significant improvement in the functional balance of all children in the intervention phase and the stability of these changes in the follow-up phase. Conclusion: Balance training by the WBB is an effective method for improving the functional balance of children with ataxic cerebral palsy. Further studies are needed using a larger sample size to confirm its effectiveness.